The mediating effect of alexithymia in the symptom burden and depression in patients with maintenance hemodialysis - Liu, Jing; Xia, Ning-ning; Wang, Hongying; Yuan, Yinying; Xiao, Leijuan; Xiang, Anne (Frontiers in Psychology, 2025)
AimThis study aimed to investigate the prevalence of alexithymia among patients receiving maintenance haemodialysis (MHD) and whether it plays a role in the relationship between symptom burden and depression in this population.BackgroundThe prevalence of depression among patients undergoing MHD is increasing. Numerous studies have found strong links between alexithymia, symptom burden, and the development of depression in this population. However, the underlying mechanisms and alexithymia's specific mediating role in the relationship between symptom burden and depression are poorly understood and have received little attention in the existing literature.MethodsThis study included 380 MHD patients in a haemodialysis center, with a mean age of 58.98 ± 13.86 years, using a self-designed patient general information questionnaire, disease-related information questionnaire, dialysis patient symptom burden scale, depression scale, and Toronto Alexithymia Scale (TAS-20). A regression model of the factors influencing depression was developed using structural equation modeling.ResultsMHD patients had a DFSSBI score of 77.41 ± 45.74, a TAS-20 score of 55.36 ± 11.17, and a Patient Health Questionnaire (PHQ-9) score of 6.07 ± 4.60. The burden of symptoms was positively correlated with alexithymia and depression (r = 0.367, 0.776, P = 0.000). The regression model had a high goodness of fit (χ2/df = 1.604, RMSEA = 0.040, GFI = 0.986, CFI = 0.999, TLI =0.997). The structural equation model analysis found the following: symptom burden was a positive predictor of alexithymia, β = 0.296, P < 0.001; alexithymia was a positive predictor of depression, β = 0.752, P < 0.001; and symptom burden was a positive predictor of depression, β = 0.141, P < 0.001.ConclusionThe level of depression in MHD patients is closely related to the burden of symptoms and alexithymia, with alexithymia serving as a partial intermediary between the two. Addressing the emotional wellbeing and symptom load of MHD patients is critical to relieving their depressive symptoms.